2013 Namibia Enterprise Survey : Country Highlights - World Bank Group (Washington, DC, 2015)
The World Bank interviewed a representative sample of the private sector in 3 of the most active economic regions in Namibia. The sample consisted of 580 business establishments surveyed from April 2014 through February 2015. The Enterprise Survey (ES) covers several topics of the business environment as well as performance measures for each firm. This report presents following highlights from the survey: Namibia’s private sector experienced strong employment growth; in Namibia, more women are engaged in the formal private sector at all levels; customs clearance takes longer for smaller firms; access to finance in Namibia appears to be less of a challenge compared to 2006; Namibia’s electricity supply is generally reliable; and access to finance and electricity continue to be the biggest obstacles to private firms’ operations.